Prayer Therapy for Reducing Labor Anxiety in Hospitals: Effective Treatment or Placebo? - Khair, Ziyadah; Hamdi, Fathul (Institut Agama Islam Negeri Parepare, 2024)
This article aims to explore the effectiveness of prayer therapy in reducing labor anxiety among pregnant women at an Islamic Hospital in Banjarmasin. The study utilizes a mixed-methods approach with a sequential explanatory design, where qualitative and quantitative data are collected in sequence to provide a comprehensive understanding of the phenomenon under investigation. Qualitative data were obtained through in-depth interviews with pregnant women and Islamic spiritual guidance officers, while quantitative data were collected using an anxiety scale questionnaire administered before and after the intervention. The results indicate that prayer therapy significantly reduces anxiety levels in pregnant women before labor. Qualitatively, the women reported increased calmness and mental preparedness following the prayer therapy, while the quantitative data showed a substantial decrease in anxiety levels post-intervention. These findings highlight the importance of integrating spiritual interventions into healthcare, particularly in religious communities. The study recommends the inclusion of prayer therapy as part of holistic childbirth programs to support the mental health of pregnant women.